Drug Users' Resilience During Rehabilitation is Strengthened Through Family Support, Personal Coping Skills, and Structured Programs Offering Diverse Therapeutic Interventions - Ayu Nur Chandra Lestari; I Nyoman Suyatna; Luh Nyoman Alit Aryani (GLOBAL HEALTH SCIENCE GROUP, 2025)
Historically, addiction treatment in the early 20th century emphasized punitive responses and abstinence-based models, often neglecting the underlying psychological and environmental contributors to substance use. In recent decades, a more holistic and integrative understanding of SUDs has emerged—one that acknowledges the significance of psychosocial dimensions in both the etiology and recovery processes. Resilience plays a critical role in the recovery process of individuals undergoing drug rehabilitation. The research employed a literature review design using a comprehensive strategy. Articles were sourced from international research journal databases accessed via the internet, specifically ScienceDirect, PubMed, and Google Scholar. All searches were conducted in May-June 2025. The keywords used in this literature review were adapted from the Medical Subject Heading (MeSH) terms, including